2014
DOI: 10.1007/s10096-014-2170-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socioeconomic risk factors on the seroprevalence of cytomegalovirus infections in a cohort of pregnant Polish women between 2010 and 2011

Abstract: The purpose of this investigation was to perform an evaluation of the prevalence and socioeconomic risk factors for human cytomegalovirus (HCMV) infections in a cohort of Polish pregnant women between 2010 and 2011. HCMV-specific IgG and IgM antibody levels were assayed with enzyme-linked immunosorbent assay (ELISA) tests in serum samples collected from 1,250 pregnant women attending outpatient obstetric clinics and hospitalized at two hospitals in Lodz. The seroprevalence of anti-HCMV IgG and IgM antibodies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
28
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 42 publications
6
28
6
Order By: Relevance
“…On the other hand, comparison of our seroprevalence with those reported in other countries suggests that the seroprevalence of CMV infection in pregnant women in Durango could be placed in an intermediate position of endemicity. The 65.6% seroprevalence found in pregnant women in Durango is similar to the 62.4%-66% seroprevalences reported in pregnant women in Poland [13], Japan [14], and Norway [15], and higher than the 49% seroprevalence in white British pregnant women in the United Kingdom [16] and a 42.3% seroprevalence in pregnant women in Germany [17]. In contrast, the seroprevalence found in pregnant women in Durango is lower than the 92.6%-100% seroprevalences reported in pregnant women in Iran [18], Palestine [19], Brazil [20], Turkey [21], Nigeria [22], and Cuba [23].…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, comparison of our seroprevalence with those reported in other countries suggests that the seroprevalence of CMV infection in pregnant women in Durango could be placed in an intermediate position of endemicity. The 65.6% seroprevalence found in pregnant women in Durango is similar to the 62.4%-66% seroprevalences reported in pregnant women in Poland [13], Japan [14], and Norway [15], and higher than the 49% seroprevalence in white British pregnant women in the United Kingdom [16] and a 42.3% seroprevalence in pregnant women in Germany [17]. In contrast, the seroprevalence found in pregnant women in Durango is lower than the 92.6%-100% seroprevalences reported in pregnant women in Iran [18], Palestine [19], Brazil [20], Turkey [21], Nigeria [22], and Cuba [23].…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, significantly higher prevalence rates of anti-HCMV IgG and IgM antibodies determined among the infected pregnant women studied in this paper, as compared to the previously reported cohort of Polish pregnant women between 2010 and 2011, as well as to other European populations, are possibly also caused by a classification of the patients to the presented study [47]. So far, it has been the first study to reveal a really significant role of TLR9 2848 G > A SNP in the occurrence of HCMV infection in pregnant women.…”
Section: Discussionsupporting
confidence: 57%
“…Human cytomegalovirus (HCMV) is the most common cause of intrauterine infections worldwide, with seroprevalence rates at the range from 40 to 100% among pregnant women [14]. Our recent study, performed among Polish pregnant women between 2010 and 2011, showed seroprevalence of anti-HCMV IgG and IgM antibodies to have been 62.4 and 2.2%, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the prevalence of CMV in childbearing-aged, pregnant and parturient women showed seroprevalence rates of 42.3% in Germany [32], 49% in the United Kingdom [35], 56.3% in Finland [36], 57% in France [22], 62.4% in Poland [37] and 91.5%-97.3% in Turkey [24,38]. Regional differences in CMV seropositivity were observed in Norway (58.5%-72.1%) [23,39] and Belgium (30%-54%) [21,31].…”
mentioning
confidence: 99%